2022
DOI: 10.1088/1674-1056/ac4e08
|View full text |Cite
|
Sign up to set email alerts
|

A 4H-SiC trench MOSFET structure with wrap N-type pillar for low oxide field and enhanced switching performance

Abstract: In this article, an optimized silicon carbide (SiC) trench Metal-Oxide-Semiconductor Field-Effect Transistor (MOSFET) structure with side-wall p-type pillar (p-pillar) and wrap n-type pillar (n-pillar) in the n-drain was investigated utilizing Silvaco TCAD simulations. The optimized structure main includes a p+ buried region, a light n-type current spreading layer (CSL), a p-type pillar region, and a wrapping n-type pillar region at the right and bottom of the p-pillar. The improved structure is named SNPPT-MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…At present, n-type 4H-SiC had achieved industrial application, while the popular size of SiC in the market was mainly 4 inches and 6 inches, but 8 inches of products were still in the process. n-type SiC can be utilized in the production of high-power devices such as MOSFETs et al [123,124]. Due to its low resistivity and high carrier concentration, high-power and efficient power based on 4H-SiC can be conversed.…”
Section: Doping Of 4h-sicmentioning
confidence: 99%
“…At present, n-type 4H-SiC had achieved industrial application, while the popular size of SiC in the market was mainly 4 inches and 6 inches, but 8 inches of products were still in the process. n-type SiC can be utilized in the production of high-power devices such as MOSFETs et al [123,124]. Due to its low resistivity and high carrier concentration, high-power and efficient power based on 4H-SiC can be conversed.…”
Section: Doping Of 4h-sicmentioning
confidence: 99%
“…Some studies have demonstrated that the trench-gate technology effectively reduces both R on,sp and the threshold voltage, primarily attributed to increased doping concentration [29][30][31][32][33][34] . As shown in Fig.…”
Section: Trench-gate Technologymentioning
confidence: 99%
“…Then the concentrations and characteristics of the bulk oxide and interface traps (e.g., energy level, capture cross-section) were initially defined in the oxide layer and the initial electron-hole density was defined to be approximately 1 × 10 13 cm −3 -1 × 10 15 cm −3 . After that, the SRH composite model, [32] Auger model, [33] CVT model, [34] Fermi-Dirac statistics model, band gap narrowing model, and bound-trap model were considered. Among them, the bound-trap model is specific for the TID effect, which enables modeling of traps coincident with ohmic boundaries.…”
Section: Modeling Of Tid Effectmentioning
confidence: 99%